2023
DOI: 10.3390/math11020353
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Risky Financial Investment Intention among Higher Education Students: A Mediating Moderating Model Using Structural Equation Modeling

Abstract: The current study examines the direct effect of investment awareness and university education support on students’ risky financial investment intentions. Additionally, it examines the mediating effect of social influence and the moderating effect of self-control on these relationships. For this purpose, we directed an online questionnaire to senior students at three public universities in Saudi Arabia. The results of SmartPLS showed positive significant effects of investment awareness and university education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
1
4
0
1
Order By: Relevance
“…After determining the nal structural equation model, path coe cients were calculated to analyze the correlation and degree of in uence of various factors on the spatial distribution of water conservancy facilities in the Grand Canal [39] .…”
Section: Resultsmentioning
confidence: 99%
“…After determining the nal structural equation model, path coe cients were calculated to analyze the correlation and degree of in uence of various factors on the spatial distribution of water conservancy facilities in the Grand Canal [39] .…”
Section: Resultsmentioning
confidence: 99%
“…Recent research on risky investment intention [42] in KSA has shown that financial knowledge has a direct effect on risky investment intention among university graduates and an indirect influence through TPB constructs. Another study [43] found a significant effect of investment awareness on investment intention. This investment knowledge of graduates is shaped by university education support [23,24].…”
Section: Green Consumption Commitment Green Knowledge Green Investmen...mentioning
confidence: 94%
“…Contrary to expectations, loss of self-control has a negative and considerable impact on investment awareness. Elshaer and Sobaih (2023) found that social-impact mediates the relationship between investment-awareness and financial-support for higher education among students. Furthermore, social impact led students to make risky financial investments.…”
Section: Introductionmentioning
confidence: 94%
“…However, it is worth noting that financial literacy significantly improved perceptions of behavioural control, subjective norms, and attitudes towards hazardous investments (Sobaih and Elshaer, 2023). Elshaer and Sobaih (2023) rightly emphasise the need to introduce a mandatory financial educational course in higher educational institutions to inform UG and PG students about wise investments and risky financial decisions.…”
Section: Introductionmentioning
confidence: 99%